A Review of Fungal Protoilludane Sesquiterpenoid Natural Products - Melissa M. Cadelis; Brent R. Copp; Siouxsie Wiles (MDPI AG, 2020)
Natural products have been a great source for drug leads, due to a vast majority possessing unique chemical structures. Such an example is the protoilludane class of natural products which contain an annulated 5/6/4-ring system and are almost exclusively produced by fungi. They have been reported to possess a diverse range of bioactivities, including antimicrobial, antifungal and cytotoxic properties. In this review, we discuss the isolation, structure elucidation and any reported bioactivities of this compound class, including establishment of stereochemistry and any total syntheses of these natural products. A total of 180 protoilludane natural products, isolated in the last 70 years, from fungi, plant and marine sources are covered, highlighting their structural diversity and potential in drug discovery.